Tensile and electrical properties of carbon nanotube yarns and knitted tubes in pure or composite form. (19th September 2008) - Hutton, Sean; Skourtis, Chris; Atkinson, Ken
Carbon Nanotubes (CNTs) have exceptionally high strength and high elastic modulus, as well as good electrical and thermal conductivity. The objective of current research is to develop new lightweight, strong, and conductive materials by using CNTs primarily in pure form. Recently, we have developed a solid-state processing method that enables the CNTs to be assembled into pure yarns and webs, avoiding the problems associated with the presence of a binder, and improving the exploitation of the inherent properties of the individual CNTs. In this paper will report on recent experience with spinning CNT yarns and the effect of twist on selected properties. We also report our results on knitted tubes, in both pure and composite form.